2022
DOI: 10.3390/ma15165657
|View full text |Cite
|
Sign up to set email alerts
|

Zeolites Reduce the Transfer of Potentially Toxic Elements from Soil to Leafy Vegetables

Abstract: The ability of natural zeolite amendment to reduce the uptake of potentially toxic elements (PTEs) by lettuce, spinach and parsley was evaluated using pot experiments. PTE concentrations in roots and shoots, as well as the pseudo total (PT), water soluble (WS) and bioavailable (BA) PTE fractions in the amended soils, were assessed. Although the PT PTE concentration was high, the WS fraction was very low (<0.4%), while the BA fraction varied widely (<5% for Cr, Mn and Co, <15% for Ni, Pb and Zn, >20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…In contrast, in the roots of sunflowers, zeolite application to soil contributed to a decrease in chromium and zinc content by 15% and 4%, respectively. The beneficial effect of zeolite application on the immobilization of trace elements in contaminated soil was also demonstrated by Cadar et al [ 79 ]. They showed that a 10% addition of this material to the soil reduced the bioaccumulation of Co, Cr, Cu, Mn, Ni, Pb, and Zn in the roots and shoots of spinach, parsley, and lettuce, with the exception of Cd in the spinach roots.…”
Section: Applications Of Zeolitesmentioning
confidence: 64%
“…In contrast, in the roots of sunflowers, zeolite application to soil contributed to a decrease in chromium and zinc content by 15% and 4%, respectively. The beneficial effect of zeolite application on the immobilization of trace elements in contaminated soil was also demonstrated by Cadar et al [ 79 ]. They showed that a 10% addition of this material to the soil reduced the bioaccumulation of Co, Cr, Cu, Mn, Ni, Pb, and Zn in the roots and shoots of spinach, parsley, and lettuce, with the exception of Cd in the spinach roots.…”
Section: Applications Of Zeolitesmentioning
confidence: 64%
“…Natural zeolites received significant attention due to their unique physicochemical properties, such as high ion exchange capacity without any structural modification, large void volume, reversible dehydration, adsorption of molecules, catalytic activity, etc. [ 30 , 33 , 50 ]. Since the cation exchange ability is expressed as the cation exchange capacity (CEC), depending on the substitution of Si by Al, the natural zeolites display a CEC value in the range 1–4 mmol M + /g zeolite [ 50 ].…”
Section: Structural and Physicochemical Characterization Of Natural A...mentioning
confidence: 99%
“…These adsorbents can remove heavy metals from polluted waters by ion exchange, chemisorption or mechanical removal [ 79 ]. Also, they were successfully applied for the remediation of the polluted soils by diminishing the mobility of the metals in soil, thus decreasing the heavy metals transfer to the plants, by the so-called “stabilization” process, without significantly altering the natural function of soils [ 33 , 43 , 80 ]. Efficiency in the environmental remediation is contingent on the type, quantity and porosity of used natural zeolites, particle size and initial concentration of contaminants, pH and ionic strength of the solution, contact time between zeolite and solution, pressure, temperature, and presence of other organic and inorganic contaminants [ 35 , 48 ].…”
Section: Fundamental Aspects Of Environmental Remediation Using Natur...mentioning
confidence: 99%
See 2 more Smart Citations